A Sharia-Based Solution to Family Planning: The Use of Temporary and Permanent Contraceptives in Light of the Legal Maxim al-Ḍararu Yuzāl - Astarina, Eva; Akmal, Andi Muhammad; Asni (MUI Sulawesi Selatan, 2024)
This study explores the permissibility and ethical considerations of contraceptive use, particularly sterilization methods like vasectomy and tubectomy, in Islamic law. The research focuses on how the Islamic legal principle al-ḍararu yuzāl (harm must be removed) applies to family planning practices, with an emphasis on temporary versus permanent contraceptive methods. It aims to offer a comprehensive understanding of how Islamic law addresses reproductive health while preserving marriage and family integrity. Using a qualitative, normative juridical approach, the study analyzes Islamic legal texts, including Qur'anic verses, Hadiths, and fatwas, in relation to contemporary contraceptive issues. A comparative analysis is employed to assess the views of Islamic scholars on contraceptive use, particularly on permanent methods like sterilization. The study also incorporates empirical data from fatwas, legal documents, and contemporary legal debates. The findings show that Islam allows the use of temporary contraceptives for birth regulation, especially for socio-economic reasons, such as ensuring adequate child care and education. However, permanent methods like sterilization are generally prohibited as they contradict the main purpose of marriage—procreation. Exceptions exist in cases of necessity, such as protecting maternal health or preventing hereditary diseases. The paper contributes to the field by offering a nuanced analysis of Islamic law regarding both temporary and permanent contraceptives, and it provides practical insights for policymakers and health professionals. The study suggests that Islamic law can offer a balanced approach to family planning, ensuring individual rights and societal welfare.